KEMENANGAN KARAENG DALAM PILKADA - Muhtar Haboddin (Jurnal Ilmu Politik dan Pemerintahan, 2011)
Paper highlights the fight elections in the District of South Sulawesi Jeneponto in 2008. Election 2008 was a battle between two major forces that exist in society which Karaeng Group (nobility) represented by Radjamilo, Agus Abdullah, and Djaini Lontang Syansuddin dealing with Zainal, Sonda Runtime, and Baharuddin Baso Tika groups representing Daeng. Brought together with the social background of each candidate pair them fight it out. Pucak of the fight then won Radjamilo of the nobility.